Post-mortem peripheral smear: A forensic diagnostic tool? - Chandra Deepak, G; Ananth Rupesh , Kattamreddy; Taqiuddin Khan , M (Journal of Indian Academy of Forensic Medicine, 2021)
The current study of post-mortem peripheral smears was conducted in Department of Forensic Medicine, Osmania Medical College with the main objective of studying the seasonal variability of autolysis of cell lines in peripheral circulation. In the study sample of 73 subjects, peripheral smears were made in the morgue immediately after collecting blood by venepuncture. Smears were stained with Leishman stain (A Romanowsky stain) within 2 hours of preparation and light microscope was used to study changes. The changes in cell morphology, membrane integrity, cytoplasmic and nuclear changes were studied in detail using valuable information from previous studies and conclusions were arrived at. At the outset white blood cells are most suitable for TSD predictability among others in peripheral smear because they withstand extraneous variables like refrigeration and show a similar degree of autolytic changes across all seasons. The validity of all such studies on cell lines for TSD was discussed from medico legal perspective. The take home message is all the microscopic changes studied in present study provided no added advantage significantly apart from traditional gross changes like rigor mortis, algor mortis, post-mortem lividity. If properly used on regular basis, algor mortis can enhance the quality of our reporting in India with respect to TSD.